Influence of wine traits and context on liking, intention to consume, wine-evoked emotions and perceived sensory sensations. (October 2021) - Sinesio, Fiorella; Moneta, Elisabetta; Di Marzo, Sabrina; Zoboli, Gian Paolo; Abbà, Silvia
Highlights: Liking and intention to consume did not vary significantly between test contexts. The context rather than the wines influenced emotional and sensory terms. Better wines' discrimination for emotional and sensory terms in HUT. Lower RATA scores in HUT context, both for positive and negative emotional terms. Better correlation between contexts for emotional terms with high level of arousal. Abstract: Wine consumption is a sensory experience that can evoke a wide range of emotional responses and heterogeneous hedonic reactions, that also depend on the circumstances in which the product is consumed. The recent literature has extensively addressed emotions elicited by wine consumption; however little research has been done on the effect of the context of consumption. This study focuses on how testing contexts and Chianti wine traits impact on liking, desire to consume again, wine-evoked emotions and perceived flavour, by comparing measurements recorded in a standard sensory laboratory (CLT), in an evoked consumption situation (images and self-description of their own habitual context of consumption) (CLT-evoked) and in a home use test in natural testing conditions (HUT), on commercial Chianti wine samples by regular consumers of red wine. The results of this study show that liking and intention to consume did not vary significantly among the test settings. This finding would suggest that the testing conditions have low relevance compared to the wine samples. However, the context influenced emotion and sensory terms. In the home use test a lowering of scores was found, both for positive and negative emotions and for sensory terms. In the HUT context a longer time for testing resulted in a better product separation. Pleasure of Chianti wine was associated with the emotions: pleasant, peaceable, joyful, amusing, and best correlated with the sensory attribute sweet . Unpleasantness was associated to the emotions: aggressive, disgusting, and overwhelming, and with the sensory terms acid, dry, astringent . Level of arousal was positively associated with euphoric, passionate, and keen, and well correlated with spicy and persistent as sensory characteristics.